Case report: Percoronary device closure of tortuous coronary artery fistula into left atrium - Sun, Shi-Bin; Kong, Zhongzheng; Farhaj, Zeeshan; Hongxin, Li (Frontiers in Cardiovascular Medicine, 2023)
Surgical ligation and transcatheter occlusion are the mainstream for the treatment of coronary artery fistulas (CAFs). However, these techniques applied to tortuous and aneurysmal CAF, especially those draining into left-heart, have their known drawbacks. We report, a successful percoronary device closure of such CAF, originating from left main coronary artery and draining into left atrium, through a left subaxillary minithoracotomy. Through a puncture on the distal straight course, we occluded CAF exclusively under transesophageal echocardiography guidance. Complete occlusion was achieved. It’s a simple, safe and effective alternative for tortuous, large and aneurysmal CAFs draining into the left heart.